Financial Reporting Standards - Doran, David T (Business Expert Press, 2012)
Ebook from IG Library ; Accounting is the score keeping system in the â€œgameâ€ of business, and you wonâ€™t do well in any â€œgameâ€ if you donâ€™t understand how the score is kept. If youâ€™re a practicing manager, MBA student, or a non-accounting business major, this book will do more than help you stay in the game.